Oportunidades e limites: a religião na Câmara Municipal de São Paulo - Correa, Everton da Silva (2019)
This work has as objective to analyze the religion bills which are under consultation at The Municipal Chamber of São Paulo between 11th and 14th legislature. After that, the author has tried to understand how secularism, as a result of religious freedom and built for over the years, allowed the city councilor through their legislative actions found the opportunity and limits to present their proposals. It was noted in spite of religious freedom does not establish a reasonable quantity of projects, a little was done by the congressmen relate to these legislatures